Cattaneo-Christov (C–C) heat flux in Darcy-Forchheimer (D-F) flow of fourth-grade nanomaterial with convective heat and mass conditions. (August 2022) - Muhammad, Khursheed; Abdelmohsen, Shaimaa A.M.; Abdelbacki, Ashraf M.M.; Aziz, A.
Abstract: Two-dimensional flow of fourth-grade nanomaterial is studied in this paper. Boungiorno model for description of nanofluid is utilized here. Flow occurs through Darcy-Forchheimer (D-F) porous medium. Further surface is subject to convective heat and mass conditions. Energy equation comprises Cattaneo-Christov (C–C) heat flux rather than Fourier's heat flux. Physical problem is modeled mathematically. By transformation technique these modeled equations are transmitted in to ODEs. OHAM (Optimal HAM) solutions methodology is adopted for computing solutions of these ODEs. Velocity, concentration, temperature, skin friction and Sherwood number are examined graphically under involved physical variables.